Composition for emulsified asphalt, emulsified asphalt and preparation method thereof, composition for waterproof coating, waterproof coating and preparation method thereof and application thereof
By using the waterproof coating prepared by the emulsified asphalt composition, the existing waterproof coatings have solved the problems of poor peeling strength, low bonding strength, poor self-healing and poor elongation of break in the repair of the asphalt roll lap edge shrinkage joint. It achieves efficient repair results and excellent performance.
Patent Information
- Application Number
- CN202410843493.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-06-27
AI Technical Summary
In the repair of the asphalt roll lap edge shrinkage joints, there are problems such as poor peel strength, low bond strength, poor self-healing and poor elongation of breakage in the existing waterproof coating.
An emulsified asphalt composition, including asphalt, saponin, emulsifier, phosphate compounds, sodium water glass and cellulose ether, is prepared by specific mixing and stirring methods, and is subsequently used for preparation. Waterproof coating.
The bonding and peeling strength between the waterproof coating and the asphalt coil is significantly improved, the bonding strength with the cement base, self-healing and elongation of breaking are achieved, and excellent performance is achieved.
Smart Images

Figure BDA0004915049250000121 
Figure BDA0004915049250000131 
Figure BDA0004915049250000141
Abstract
Description
Technical Field
[0001] The present invention relates to the field of waterproof coatings, and in particular to a composition for emulsified asphalt, emulsified asphalt and a preparation method thereof, a composition for waterproof coatings, a waterproof coating and a preparation method and application thereof. Background Art
[0002] In recent years, with the development of national construction and the increasing requirements for the quality of building materials, as well as the formulation of relevant national standards for waterproof materials and the increased efforts of the country to promote new building waterproof materials, "polyester base polymer modified asphalt membrane" has become synonymous with high-quality asphalt-based waterproof materials.
[0003] However, when the polyester base is used in actual production, the coil shrinks greatly. Although many manufacturers use the method of widening the base material to offset the size shrinkage during the coil production process and make the finished product width qualified, the internal stress of the coil caused by the excessive shrinkage of the base cannot be reduced, causing the coil to deform under the condition of secondary heating during construction.
[0004] Research has found that the difference in the degree of heat focus on modified asphalt membranes due to light exposure (daytime) and non-light exposure (nighttime) causes the temperature difference of the material to be more than 35 degrees Celsius (here refers to the material temperature rather than the ambient temperature), and if the membrane is laid over a large area in this environment, the overlap edges are likely to shrink.
[0005] If the shrinkage of the overlapped edge of the waterproofing membrane is not repaired, water is very likely to enter the gap between the waterproofing membrane and the base layer along the damaged overlapped seams or cracks of the waterproofing membrane, causing water seepage, resulting in the loss of the waterproofing layer and increasing the risk of water leakage in the building.
[0006] CN 117143574 A discloses an asphalt shale inhibitor which meets the use requirements of deep well operations and is safer and more environmentally friendly. The asphalt shale inhibitor comprises the following raw materials, measured by weight: 40 to 55 parts of natural asphalt, 18 to 25 parts of petroleum asphalt, 8 to 15 parts of a modifier and 1 to 10 parts of a solubilizer; the modifier is prepared by using saponin powder, fly ash and a coupling agent in a weight ratio of (8 to 15):(3 to 6):(0.1 to 2).
[0007] At present, waterproof coatings that can be used to repair the shrinkage of the overlapped edges of roll materials have problems such as poor peeling strength with asphalt roll materials, low bonding strength with cement-based materials, and poor self-healing properties. Summary of the invention
[0008] The purpose of the present invention is to overcome the problems existing in the prior art of poor peeling strength between waterproof coating and asphalt coil, low bonding strength with cement base, poor self-healing property and poor elongation at break.
[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composition for emulsified asphalt, which contains asphalt, saponin liquid, emulsifier, phosphate compound, sodium water glass and cellulose ether;
[0010] The content of saponin in the saponin liquid is 0.035-0.045wt%, and the content of saponin phenol is 0.003-0.09wt%;
[0011] Based on the total mass of the composition, the content of the asphalt is 60-74wt%, the content of the soap liquid is 22-35wt%, the content of the emulsifier is 2-4wt%, the content of the phosphate compound is 0.15-0.45wt%, the content of the sodium water glass is 0.2-0.4wt% and the content of the cellulose ether is 0.25-0.5wt%.
[0012] A second aspect of the present invention provides a method for preparing emulsified asphalt, using the components of the emulsified asphalt composition, the method comprising:
[0013] (1) in the presence of water, an emulsifier, a saponin solution, sodium water glass and a phosphate compound are first stirred and mixed to obtain a mixture I;
[0014] (2) subjecting the mixture I to a second stirring mixing with asphalt to obtain a mixture II;
[0015] (3) subjecting the mixture II and the cellulose ether to a third stirring mixing to obtain the emulsified asphalt;
[0016] The composition for emulsified asphalt is the composition for emulsified asphalt described in the first aspect above.
[0017] The third aspect of the present invention provides emulsified asphalt prepared by the method described in the second aspect.
[0018] A fourth aspect of the present invention provides a waterproof coating composition, which contains styrene-butadiene emulsion, aqueous polyurethane emulsion, acrylic emulsion, talcum powder, organic bentonite, thickener, dispersant, defoamer, preservative, film-forming aid and emulsified asphalt;
[0019] Based on the total mass of the composition, the content of the styrene-butadiene emulsion is 4-8wt%, the content of the aqueous polyurethane emulsion is 14-18wt%, the content of the acrylic emulsion is 8-12wt%, the content of the talc is 18-25wt%, the content of the organic bentonite is 7-10wt%, the content of the thickener is 0.1-0.3wt%, the content of the dispersant is 0.2-0.4wt%, the content of the defoamer is 0.2-0.4wt%, the content of the preservative is 0.1-0.35wt%, the content of the film-forming aid is 0.1-0.3wt% and the content of the emulsified asphalt is 28-35wt%;
[0020] The emulsified asphalt is the emulsified asphalt described in the third aspect above.
[0021] A fifth aspect of the present invention provides a method for preparing a waterproof coating, which is carried out using the components of the waterproof coating composition, and the method comprises:
[0022] S1: In the presence of water, styrene-butadiene emulsion, aqueous polyurethane emulsion, acrylic emulsion, talcum powder, organic bentonite, thickener and dispersant are mixed I to obtain material I;
[0023] S2: In the presence of a pH regulator, mixing the material I with a defoamer, a preservative, and a film-forming aid to obtain a material II;
[0024] S3: mixing the material II with emulsified asphalt to obtain the waterproof coating;
[0025] And / or, the conditions of the mixing I include: temperature of 5-40°C and time of 25-60min;
[0026] And / or, the conditions of the mixing II include: temperature of 5-40°C and time of 10-30min;
[0027] And / or, the conditions of mixing III include: temperature of 5-40°C and time of 10-30min;
[0028] The waterproof coating composition is the waterproof coating composition described in the fourth aspect.
[0029] The sixth aspect of the present invention provides a waterproof coating prepared by the method described in the fifth aspect.
[0030] The seventh aspect of the present invention provides the use of the waterproof coating described in the sixth aspect in the repair of shrinkage joints at the lap edges of asphalt membranes.
[0031] Through the above technical solution, the present invention has at least the following advantages:
[0032] (1) The waterproof coating provided by the present invention has excellent properties such as high bonding peel strength with asphalt roll materials, high bonding strength with cement-based materials, good self-healing properties, and high elongation at break.
[0033] (2) The waterproof coating provided by the present invention is easy to use. DETAILED DESCRIPTION
[0034] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0035] As mentioned above, the first aspect of the present invention provides a composition for emulsified asphalt, which contains asphalt, saponin solution, emulsifier, phosphate compound, sodium water glass and cellulose ether;
[0036] The content of saponin in the saponin liquid is 0.035-0.045wt%, and the content of saponin phenol is 0.003-0.09wt%;
[0037] Based on the total mass of the composition, the content of the asphalt is 60-74wt%, the content of the soap liquid is 22-35wt%, the content of the emulsifier is 2-4wt%, the content of the phosphate compound is 0.15-0.45wt%, the content of the sodium water glass is 0.2-0.4wt% and the content of the cellulose ether is 0.25-0.5wt%.
[0038] Preferably, the emulsifier is a sulfate type. More preferably, the emulsifier is 2-methyl-2-acrylic acid sodium salt.
[0039] Preferably, the phosphate compound is sodium hexametaphosphate and / or sodium pyrophosphate.
[0040] Preferably, the asphalt is a combination of No. 10 asphalt and No. 70 asphalt in a mass ratio of 1:1.6-2.5.
[0041] Preferably, the saponin liquid is a product obtained by extracting dry saponins and water in a mass ratio of 1:5-8; the extraction conditions of the saponin liquid include: a temperature of 80-100°C and a time of 3-5h.
[0042] Preferably, the soapnut liquid is prepared by a method comprising the following steps: grinding dry soapnuts into particles of 180 μm-425 μm, then extracting the particles with water in a mass ratio of 1:5-8 to obtain an extract, passing the extract through a Chinese standard sieve of 80-200 mesh, taking the material under the sieve to obtain the soapnut liquid.
[0043] More preferably, the water content of the dry soap locust is ≤5wt%, and the content of saponin in the dry soap locust is ≥2mg / g.
[0044] Further preferably, the origin of the dry soap beans is selected from at least one of Henan Province, Shandong Province and Yunnan Province.
[0045] As mentioned above, the second aspect of the present invention provides a method for preparing emulsified asphalt, using the components of the emulsified asphalt composition, the method comprising:
[0046] (1) in the presence of water, an emulsifier, a saponin solution, sodium water glass and a phosphate compound are first stirred and mixed to obtain a mixture I;
[0047] (2) subjecting the mixture I to a second stirring mixing with asphalt to obtain a mixture II;
[0048] (3) subjecting the mixture II and the cellulose ether to a third stirring mixing to obtain the emulsified asphalt;
[0049] The composition for emulsified asphalt is the composition for emulsified asphalt described in the first aspect above.
[0050] Preferably, the modulus of the sodium water glass is 35-40 and the density is 1.3-1.5 g / cm 3 .
[0051] Preferably, based on the total mass of the composition, the amount of the asphalt is 60-74wt%, the amount of the soap liquid is 22-35wt%, the amount of the emulsifier is 2-4wt%, the amount of the phosphate compound is 0.15-0.45wt%, the amount of the sodium water glass is 0.2-0.4wt% and the amount of the cellulose ether is 0.25-0.5wt%.
[0052] Preferably, the first stirring and mixing conditions include: temperature of 5-40° C. and time of 5-10 min.
[0053] Preferably, the second stirring and mixing conditions include: temperature of 60-80° C. and time of 2-5 min.
[0054] Preferably, the third stirring and mixing conditions include: temperature of 5-40° C. and time of 10-30 min.
[0055] According to a particularly preferred embodiment, the method further comprises, in step (1), preheating the saponin liquid to 75-85° C., and then first stirring and mixing water, emulsifier, sodium water glass, phosphate compound and the preheated saponin liquid to obtain mixture I.
[0056] It should be noted that the first stirring and mixing time in the present invention does not include the time for preheating the soapnut liquid.
[0057] Preferably, in step (1), the present invention has no specific requirement on the amount of water used, and any amount known in the art may be used.
[0058] Preferably, the first stirring and mixing condition also includes: a rotation speed of 600-800 rpm.
[0059] According to a particularly preferred embodiment, the method further comprises, in step (2), preheating the asphalt to 130-140° C., and then subjecting the preheated asphalt and the mixture I to a second stirring mixing to obtain a mixture II.
[0060] It should be noted that the second stirring and mixing time in the present invention does not include the time for preheating the asphalt.
[0061] Preferably, the second stirring and mixing condition also includes: a rotation speed of 4000-5000 rpm.
[0062] According to a preferred embodiment, the method further comprises, in step (3), firstly mixing cellulose ether with water in a mass ratio of 1:2-4 to obtain a premix, and then subjecting the mixture II and the premix to a third stirring mixing.
[0063] Preferably, the third stirring and mixing condition also includes: a rotation speed of 1000-1500 rpm.
[0064] In order to obtain emulsified asphalt with better dispersibility, according to a preferred specific implementation, the method further includes performing a fourth stirring and mixing of the mixture obtained after the third stirring and mixing with water to obtain the emulsified asphalt.
[0065] It should be noted that the present invention has no special requirements on the amounts of the water and the mixture, and any amounts known in the art may be used.
[0066] Preferably, the fourth stirring and mixing conditions include: temperature of 5-40° C., time of 3-10 min, and rotation speed of 400-600 rpm.
[0067] As mentioned above, the third aspect of the present invention provides emulsified asphalt prepared by the method described in the second aspect.
[0068] As mentioned above, the fourth aspect of the present invention provides a waterproof coating composition, which contains styrene-butadiene emulsion, aqueous polyurethane emulsion, acrylic emulsion, talcum powder, organic bentonite, thickener, dispersant, defoamer, preservative, film-forming aid and emulsified asphalt;
[0069] Based on the total mass of the composition, the content of the styrene-butadiene emulsion is 4-8wt%, the content of the aqueous polyurethane emulsion is 14-18wt%, the content of the acrylic emulsion is 8-12wt%, the content of the talc is 18-25wt%, the content of the organic bentonite is 7-10wt%, the content of the thickener is 0.1-0.3wt%, the content of the dispersant is 0.2-0.4wt%, the content of the defoamer is 0.2-0.4wt%, the content of the preservative is 0.1-0.35wt%, the content of the film-forming aid is 0.1-0.3wt% and the content of the emulsified asphalt is 28-35wt%;
[0070] The emulsified asphalt is the emulsified asphalt described in the third aspect above.
[0071] Preferably, the kinematic viscosity of the dispersant at 25° C. is 20-500 cps.
[0072] More preferably, the dispersant is a sodium polyacrylate dispersant, and the sodium polyacrylate dispersant contains 40-50 wt % of polyacrylate.
[0073] Preferably, the thickener is at least one of hydroxyethyl cellulose, methyl cellulose, carboxymethyl cellulose and hydroxypropyl methyl cellulose;
[0074] Preferably, the film-forming aid is at least one of 2,2,4-trimethyl-1,3-pentanediol-isobutyric acid monoester, ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol n-butyl ether, propylene glycol phenyl ether, ethylene glycol butyl ether acetate, and 3-ethoxyethyl propionate.
[0075] As mentioned above, the fifth aspect of the present invention provides a method for preparing a waterproof coating, which is carried out using the components of the waterproof coating composition, and the method comprises:
[0076] S1: In the presence of water, styrene-butadiene emulsion, aqueous polyurethane emulsion, acrylic emulsion, talcum powder, organic bentonite, thickener and dispersant are mixed I to obtain material I;
[0077] S2: In the presence of a pH regulator, mixing the material I with a defoamer, a preservative, and a film-forming aid to obtain a material II;
[0078] S3: mixing the material II with emulsified asphalt to obtain the waterproof coating;
[0079] And / or, the conditions of the mixing I include: temperature of 5-40°C and time of 25-60min;
[0080] And / or, the conditions of the mixing II include: temperature of 5-40°C and time of 10-30min;
[0081] And / or, the conditions of mixing III include: temperature of 5-40°C and time of 10-30min;
[0082] The waterproof coating composition is the waterproof coating composition described in the fourth aspect.
[0083] Preferably, in step S1, the average particle diameter of the talcum powder is 5-20 μm.
[0084] Preferably, in step S2, the pH adjuster is Dow AMP-95.
[0085] Preferably, in step S2, the defoaming agent is a silicone defoaming agent.
[0086] Preferably, in step S2, the preservative is isothiazolinone.
[0087] Preferably, based on the total amount of the composition, the amount of the styrene-butadiene emulsion is 4-8wt%, the amount of the aqueous polyurethane emulsion is 14-18wt%, the amount of the acrylic emulsion is 8-12wt%, the amount of the talc is 18-25wt%, the amount of the organic bentonite is 7-10wt%, the amount of the thickener is 0.1-0.3wt%, the amount of the dispersant is 0.2-0.4wt%, the amount of the defoamer is 0.2-0.4wt%, the amount of the preservative is 0.1-0.35wt%, the amount of the film-forming aid is 0.1-0.3wt% and the amount of the emulsified asphalt is 28-35wt%.
[0088] Preferably, the method further comprises, in step S1, first dispersing the styrene-butadiene emulsion, the aqueous polyurethane emulsion and the acrylic emulsion in the presence of water, and then mixing the obtained dispersion with talcum powder, organic bentonite, a thickener and a dispersant I to obtain material I.
[0089] Preferably, the dispersion conditions include: temperature of 5-40°C, time of 25-35 min, and rotation speed of 800-1400 rpm.
[0090] It should be noted that the mixing time of the present invention does not include the dispersion time.
[0091] Preferably, in step S2, the amount of the pH adjuster is such that the pH of the material II is 8-10.
[0092] In order to obtain a waterproof coating with better peeling strength with asphalt roll materials and stronger bonding strength with cement-based materials, according to a preferred specific embodiment, the method also includes, after the mixing III, passing the mixture obtained by the mixing III through a 50-100 mesh Chinese standard sieve, taking the material under the sieve to obtain the waterproof coating.
[0093] Preferably, the step S1, the step S2 and the step S3 are all performed under stirring conditions, the stirring rates of the step S1 and the step S2 are each independently 800-1400 rpm, and the stirring rate of the step S3 is 500-800 rpm.
[0094] As mentioned above, the sixth aspect of the present invention provides a waterproof coating prepared by the method described in the fifth aspect.
[0095] As mentioned above, the seventh aspect of the present invention provides the use of the waterproof coating described in the sixth aspect in the repair of shrinkage joints at the lap edges of asphalt membranes.
[0096] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the instruments, reagents, materials, etc. involved are conventional instruments, reagents, materials, etc., which can be obtained through regular commercial channels.
[0097] Raw materials for preparing emulsified asphalt:
[0098] Asphalt I is a combination of No. 10 asphalt and No. 70 asphalt in a mass ratio of 1:1.9;
[0099] Asphalt II is a combination of No. 10 asphalt and No. 70 asphalt in a mass ratio of 1:2.4;
[0100] Asphalt III is a combination of No. 10 asphalt and No. 60 asphalt in a mass ratio of 1:1.9;
[0101] Among them, No. 10 asphalt was purchased from Alpha Company; No. 70 asphalt was purchased from Alpha Company; No. 60 asphalt was purchased from Alpha Company;
[0102] Dry saponin: average particle diameter is 250 μm, moisture content is 0.05 wt%, saponin content is 2.5 mg / g, origin is Henan Province;
[0103] Sodium water glass: modulus is 35, density is 1.2g / cm 3 , purchased from Jinan Zesheng Chemical Co., Ltd.;
[0104] Phosphate compounds: sodium hexametaphosphate, purchased from Weifang Chenyang Chemical Co., Ltd.;
[0105] Emulsifier: brand PION NS-8-4A, purchased from Shandong Pion Road and Bridge Materials Co., Ltd.;
[0106] Cellulose ether: Hydroxyethyl cellulose, brand B30K, purchased from Lotte Chemical of South Korea.
[0107] Raw materials for preparing waterproof coatings:
[0108] Styrene butadiene emulsion: brand 7809, purchased from BASF SE;
[0109] Waterborne polyurethane emulsion: brand 5619LA, purchased from Shanghai Baolijia Chemical Co., Ltd.;
[0110] Acrylic emulsion: brand 300SL, purchased from Badfu Group Co., Ltd.
[0111] Talc: The average particle diameter was 13 μm and it was purchased from Chongqing Zhiduo New Building Materials Co., Ltd.
[0112] Organic bentonite: purchased from Wuhu Shuohua New Material Technology Co., Ltd.;
[0113] Thickener: Hydroxyethyl cellulose, brand B30K, purchased from Lotte Chemical, South Korea;
[0114] Dispersant: polyacrylic acid sodium salt dispersant, the content of polyacrylic acid salt is 45wt%, the kinematic viscosity at 25°C is 450cps, purchased from San Nopco, Japan, model SN-Dispersant SN5040;
[0115] Defoamer: silicone defoamer, the active ingredient is polydimethylsiloxane, purchased from Jiangsu Jianyu Additive Technology Co., Ltd., model JY-810;
[0116] Preservative: isothiazolinone, brand name MERGAL K14, purchased from Troy Company, USA;
[0117] Film-forming aid: 2,2,4-trimethyl-1,3-pentanediol-isobutyric acid monoester, model TEXANOL, purchased from Eastman Chemical Company;
[0118] pH adjuster: AMP-95, purchased from Dow Chemical;
[0119] Oleanolic acid standard: purchased from Wuhan Tianzhi Biotechnology Co., Ltd.
[0120] The A series preparation examples of the present invention are used to prepare saponin liquid, and the total amount of dry saponin and water used in this series of preparation examples is 500g.
[0121] Preparation Example A1
[0122] The dried sapodillas were extracted with water in a mass ratio of 1:6 to obtain an extract, and then the extract was passed through a 100-mesh Chinese standard sieve, and the material under the sieve was taken to obtain sapodilla liquid I.
[0123] The extraction conditions were: temperature 100°C, time 4h.
[0124] The content of saponin in the saponin liquid I is 0.042wt%, and the content of saponin phenol is 0.045wt%.
[0125] Preparation Example A2
[0126] The dried sapodillas were extracted with water in a mass ratio of 1:7 to obtain an extract, and then the extract was passed through a 100-mesh Chinese standard sieve, and the material under the sieve was taken to obtain sapodilla liquid II.
[0127] The extraction conditions were: temperature 90°C and time 4.5 h.
[0128] The content of saponin in the saponin liquid II is 0.036 wt %, and the content of saponin phenol is 0.04 wt %.
[0129] The B series preparation examples of the present invention are used to prepare emulsified asphalt. The amounts of raw materials used in this series of preparation examples are all parts by weight unless otherwise specified, and each part by weight represents 10 g.
[0130] Preparation Example B1
[0131] (1) preheating a saponin solution to 80° C., and then stirring and mixing water (100 g), sodium water glass, a phosphate compound, and the preheated saponin solution to obtain a mixture I;
[0132] (2) preheating the asphalt to 135° C. and then stirring and mixing the preheated asphalt and the mixture I for a second time to obtain a mixture II;
[0133] (3) First, cellulose ether and water are mixed in a mass ratio of 1:3 to obtain a premix, and then the mixture II and the premix are subjected to a third stirring and mixing process. Then, the mixture obtained after the third stirring and mixing is subjected to a fourth stirring and mixing process with water (49 g) to obtain emulsified asphalt L1.
[0134] The types, amounts and process parameters of the substances involved in this preparation example are listed in Table 1.
[0135] Unless otherwise specified, the other B series preparation examples are carried out in accordance with the method of Preparation Example B1, except that the raw materials and process parameters used in each B series preparation example are not the same, and the specific details are shown in Table 1.
[0136] Table 1
[0137]
[0138] Preparation Example B3
[0139] This preparation example is carried out in a similar manner to Preparation Example B1, except that the asphalt I in Preparation Example B1 is replaced with an equal weight portion of asphalt III to obtain emulsified asphalt L3.
[0140] Comparative Preparation Example DB1
[0141] This comparative preparation example is carried out in a similar manner to Preparation Example B1, except that the amount of saponin liquid I in this comparative example is adjusted to 36 parts by weight, and the amount of asphalt I is adjusted to 60.62 parts by weight, to obtain emulsified asphalt D-L1.
[0142] Comparative Preparation Example DB2
[0143] This comparative preparation example is carried out in a similar manner to Preparation Example B1, except that the saponin liquid I in Preparation Example B1 is replaced with an equal weight portion of oleanolic acid solution (the mass fraction of oleanolic acid in the solution is 0.042wt%) to obtain emulsified asphalt D-L2.
[0144] Unless otherwise specified, the amounts of raw materials used in the following examples are all parts by weight, and each part by weight represents 10 g.
[0145] Example
[0146] S1: In the presence of water (120 g), a styrene-butadiene emulsion, an aqueous polyurethane emulsion, and an acrylic emulsion are first dispersed, and then the obtained dispersion is mixed with talcum powder, organic bentonite, a thickener, and a dispersant to obtain material I;
[0147] The dispersion conditions were: temperature 25 °C, time 25 min, and rotation speed 1000 rpm;
[0148] S2: In the presence of a pH regulator, mixing the material I with a defoamer, a preservative, and a film-forming aid to obtain a material II;
[0149] S3: Mixing the material II with the emulsified asphalt III, passing the mixture obtained by mixing III through a Chinese standard sieve of 80 mesh, taking the material under the sieve to obtain a waterproof coating.
[0150] The types, amounts and process parameters of the substances involved in this example are listed in Table 2.
[0151] Unless otherwise specified, the remaining examples are carried out in accordance with the method of Example 1, except that the raw materials and process parameters used in each example are different, and the specific details are shown in Table 2.
[0152] Table 2
[0153]
[0154]
[0155] Example 3
[0156] This embodiment is carried out in a similar manner to that of Embodiment 1, except that the emulsified asphalt L1 in Embodiment 1 is replaced with an equal weight portion of emulsified asphalt L3 to prepare a waterproof coating.
[0157] Example 4
[0158] This example is carried out in a similar manner to that of Example 1, except that the amount of emulsified asphalt in this example is adjusted to 36 parts by weight, and the amount of aqueous polyurethane emulsion is adjusted to 14.4 parts by weight to prepare a waterproof coating.
[0159] Example 5
[0160] This example is carried out in a similar manner to that of Example 1, except that the amount of the aqueous polyurethane emulsion in this example is adjusted to 28 parts by weight, and the amount of the acrylic emulsion is adjusted to 0 parts by weight, to prepare a waterproof coating.
[0161] Example 6
[0162] This embodiment is carried out in a similar manner to that of Embodiment 1, except that the emulsified asphalt L1 in Embodiment 1 is replaced with an equal weight portion of emulsified asphalt L4 to prepare a waterproof coating.
[0163] Comparative Example 1
[0164] This comparative example is carried out in a similar manner to Example 1, except that the emulsified asphalt L1 in Example 1 is replaced with an equal weight portion of emulsified asphalt D-L1 to prepare a waterproof coating.
[0165] Comparative Example 2
[0166] This comparative example is carried out in a similar manner to Example 1, except that the emulsified asphalt L1 in Example 1 is replaced with an equal weight portion of emulsified asphalt D-L2 to prepare a waterproof coating.
[0167] Test Case
[0168] The performance of the waterproof coating prepared in the above example was tested according to the test method of JCT 408-2005 "Water-emulsified asphalt waterproof coating". The test results are shown in Table 3.
[0169] Table 3
[0170]
[0171]
[0172] Table 3
[0173]
[0174]
[0175] It can be seen from the data in Table 3 that the waterproof coating provided by the present invention has excellent properties such as high bonding peel strength with asphalt coil, high bonding strength with cement base, good self-healing property, and high elongation at break.
[0176] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A composition for emulsified asphalt, characterized in that: The composition contains asphalt, saponin liquid, emulsifier, phosphate compound, sodium water glass and cellulose ether; The content of saponin in the saponin solution is 0.035-0.045wt%, and the content of saponin is 0.003-0.09wt%; Based on the total mass of the composition, the content of the asphalt is 60-74wt%, the content of the soap solution is 22-35wt%, the content of the emulsifier is 2-4wt%, the content of the phosphate compound is 0.15-0.45wt%, the content of the sodium water glass is 0.2-0.4wt% and the content of the cellulose ether is 0.25-0.5wt%; The saponin liquid is a product obtained by extracting dry saponins and water in a mass ratio of 1:5-8; The extraction conditions of the saponin liquid include: temperature of 80-100° C. and time of 3-5 hours.
2. The composition according to claim 1, wherein The emulsifier is of sulfate type; And / or, the phosphate compound is sodium hexametaphosphate and / or sodium pyrophosphate; And / or, the asphalt is a combination of No. 10 asphalt and No. 70 asphalt in a mass ratio of 1:1.6-2.
5.
3. A method for preparing emulsified asphalt, characterized in that: The method is carried out by applying the components of the emulsified asphalt composition, and comprises: (1) in the presence of water, an emulsifier, a saponin solution, sodium water glass and a phosphate compound are first stirred and mixed to obtain a mixture I; (2) subjecting the mixture I to a second stirring mixing with asphalt to obtain a mixture II; (3) performing a third stirring mixing on the mixture II and the cellulose ether to obtain the emulsified asphalt; The composition for emulsified asphalt is the composition for emulsified asphalt according to claim 1 or 2.
4. The method according to claim 3, wherein: The first stirring and mixing conditions include: temperature of 5-40°C and time of 5-10 minutes; And / or, the second stirring and mixing conditions include: temperature of 60-80° C., time of 2-5 min; And / or, the third stirring and mixing conditions include: temperature of 5-40° C. and time of 10-30 min.
5. Emulsified asphalt prepared by the method described in claim 3 or 4.
6. A waterproof coating composition, characterized in that: The composition contains styrene-butadiene emulsion, water-based polyurethane emulsion, acrylic emulsion, talcum powder, organic bentonite, thickener, dispersant, defoamer, preservative, film-forming aid and emulsified asphalt; Based on the total mass of the composition, the content of the styrene-butadiene emulsion is 4-8wt%, the content of the aqueous polyurethane emulsion is 14-18wt%, the content of the acrylic emulsion is 8-12wt%, the content of the talc is 18-25wt%, the content of the organic bentonite is 7-10wt%, the content of the thickener is 0.1-0.3wt%, the content of the dispersant is 0.2-0.4wt%, the content of the defoamer is 0.2-0.4wt%, the content of the preservative is 0.1-0.35wt%, the content of the film-forming aid is 0.1-0.3wt% and the content of the emulsified asphalt is 28-35wt%; The emulsified asphalt is the emulsified asphalt according to claim 5.
7. The composition according to claim 6, wherein The kinematic viscosity of the dispersant at 25° C. is 20-500 cps; And / or, the thickener is at least one of hydroxyethyl cellulose, methyl cellulose, carboxymethyl cellulose, and hydroxypropyl methyl cellulose; And / or, the film-forming aid is at least one of 2,2,4-trimethyl-1,3-pentanediol-isobutyric acid monoester, ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol n-butyl ether, propylene glycol phenyl ether, ethylene glycol butyl ether acetate, and 3-ethoxyethyl propionate.
8. The composition according to claim 7, wherein The dispersant is a sodium polyacrylate dispersant, and the sodium polyacrylate dispersant contains 40-50 wt % of polyacrylate.
9. A method for preparing a waterproof coating, characterized in that: The method is carried out by applying the components of the waterproof coating composition, and the method comprises: S1: In the presence of water, styrene-butadiene emulsion, aqueous polyurethane emulsion, acrylic emulsion, talcum powder, organic bentonite, thickener and dispersant are mixed I to obtain material I; S2: In the presence of a pH regulator, mixing the material I with a defoamer, a preservative, and a film-forming aid to obtain a material II; S3: mixing the material II with emulsified asphalt to obtain the waterproof coating; The waterproof coating composition is the waterproof coating composition according to claim 6 or 7.
10. The method according to claim 9, wherein: The mixing conditions of the mixing I include: temperature of 5-40° C. and time of 25-60 min.
11. The method according to claim 9 or 10, wherein: The conditions of the mixing II include: temperature of 5-40° C. and time of 10-30 min.
12. The method according to claim 9 or 10, wherein: The conditions of mixing III include: temperature of 5-40° C. and time of 10-30 min.
13. A waterproof coating prepared by the method according to claim 9.
14. Use of the waterproof coating according to claim 13 in the repair of shrinkage joints at the overlapped edges of asphalt coiled materials.
Citation Information
Patent Citations
Asphalt shale inhibitor as well as preparation method and application thereof
CN117143574A
Water-based base layer treating agent composition, water-based base layer treating agent and preparation method and application of water-based base layer treating agent
CN113502126A
Water-based bio-based alkyd emulsion based on renewable vegetable pitch and preparation method thereof
CN113736335A